Relasi Harmonis Tuhan dan Manusia, dalam Perspektif Al-Quran (Konsep Merindu Allah) - Agung Pratama, Ramadhana; Taufik, M; Fadli, Adi (Jurnal el-Huda, 2024)
Abstract: The relationship between God and humans is a fundamental theme in various religious and philosophical traditions. This concept reflects humans' attempts to understand the existence of God as a transcendent entity and how this relationship shapes their life experiences. This relationship is often understood in two main dimensions: vertical and horizontal. The vertical dimension emphasizes the transcendental aspect of God, where humans try to get closer to God through worship, prayer, and spiritual reflection. Meanwhile, the horizontal dimension highlights the manifestation of this relationship in social life, such as through love, kindness, and justice for others. Each religious tradition has a unique interpretation of this relationship, whether through the concept of creation, covenant, or God's unconditional love. On the other hand, in philosophy, this relationship is often studied from an existentialist perspective, where humans try to understand the purpose of their existence through their connection with a greater entity. Thus, the relationship between God and humans becomes the basis for the search for the meaning of life, morality, and social order. This study aims to analyze various perspectives on this relationship, bridging the theological, philosophical, and humanistic dimensions to reveal its relevance in the modern context.